2008
DOI: 10.1111/j.1550-7408.2008.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Growth of Hyphochytrium catenoides after Exposure to Environmental Stress

Abstract: The survival of an isolate of Hyphochytrium catenoides collected from soil in the Blue Mountains in eastern New South Wales, Australia, was tested under extreme conditions in the laboratory. This isolate recovered growth after being subjected to drying on filter paper, to heat while desiccated, to hypersalinity, to strict anaerobic conditions, to freezing temperatures, and to a short period in solutions at pH 2.8-11.2. The capacity to survive under these conditions in the laboratory suggests adaptation to fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Ribosomal DNA sequences have been recorded in public databases for only three isolates: two in the genus Hyphochytrium (van der Auwera et al 1995;Gleason et al 2008b); and one in the genus Rhizidiomyces (Hausner et al 2000). No sequences are currently available for species in the Anisolpidiaceae .…”
Section: Hyphochytriomycotamentioning
confidence: 99%
See 1 more Smart Citation
“…Ribosomal DNA sequences have been recorded in public databases for only three isolates: two in the genus Hyphochytrium (van der Auwera et al 1995;Gleason et al 2008b); and one in the genus Rhizidiomyces (Hausner et al 2000). No sequences are currently available for species in the Anisolpidiaceae .…”
Section: Hyphochytriomycotamentioning
confidence: 99%
“…Environmental rDNA surveys showed that small heterotrophic fl agellates (HFs) are a heterogeneous assemblage mainly composed of zoospores of parasitic and saprotrophic zoosporic fungi, alveolates (e.g., perkinsids) and stramenopiles (Gleason et al 2008b;Sime-Ngando et al 2011). Thus, zoospores signifi cantly contribute to the pool of HFs in the marine plankton .…”
Section: Ecological Role and Importancementioning
confidence: 99%